Розробка засобів пеленгації БЛА тактичного (окопного) рівня на основі sdr радіо - Бохан, І. А.; Лихограй, В. Г.; Тухтаров, В. Б. (ХНУРЕ, 2024)
In connection with the aggression of the Russian Federation against Ukraine and the possible aggression of the Russian Federation against NATO countries, based on the active development of radio-controlled unmanned systems of the Armed Forces of the Russian Federation, this work examines the existing and prospective developments of direction-finding means of unmanned aerial vehicles (UAV) of the tactical level of the armed forces of the Russian Federation.
Keywords: пеленгація БЛА; sdr радіо